2017
DOI: 10.1021/acsami.7b12697
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Cross-Linked MOF Membrane Generated from Imidazolium-Based Ionic Liquid-Decorated UiO-66 Type NMOF and Its Application toward CO2 Separation and Conversion

Abstract: Carbon dioxide capture and transformation are of great importance to make cuts in greenhouse gas emissions. Nanometal-organic frameworks (NMOFs) could serve as ideal fillers for polymer membranes owing to their structural diversity and regulable microenvironment of the nanocage. Herein, a bifunctional, robust, and chemically cross-linked NMOF-based membrane was successfully constructed by the postsynthetic polymerization of imidazolium-based ionic liquid (IL)-decorated UiO-66 type nanoparticles (NPs) and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 81 publications
1
56
0
Order By: Relevance
“…On the other hand, the chemical exploitation of carbon dioxide, an abundant, available, and nontoxic source of carbon, has been widely employed as an alternative sustainable approach in the synthesis of fine chemicals. , Acid-catalyzed cycloaddition of CO 2 and epoxides is a highly atom-economical process to convert CO 2 into cyclic organic carbonates . Numerous studies have been devoted to the development of efficient heterogeneous catalysts, including porous carbons, zeolites, ionic liquid-supported solids, silica-supported solids, polymers, and MOFs. However, there are some shortcomings when exploiting the chemical fixation of CO 2 , such as the addition of organic solvent, the need for elevated pressure, harsh reaction conditions (high temperature and long reaction time), and/or low catalytic activity. , Thus, the development of new heterogeneous acidic catalysts to synthesize cyclic carbonates utilizing CO 2 as a building block is still of great interest. Moreover, developing a one-pot synthesis of cyclic carbonates from olefins and CO 2 is a highly desirable and economical approach because this reaction uses readily available olefins without the need for preliminary epoxide synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the chemical exploitation of carbon dioxide, an abundant, available, and nontoxic source of carbon, has been widely employed as an alternative sustainable approach in the synthesis of fine chemicals. , Acid-catalyzed cycloaddition of CO 2 and epoxides is a highly atom-economical process to convert CO 2 into cyclic organic carbonates . Numerous studies have been devoted to the development of efficient heterogeneous catalysts, including porous carbons, zeolites, ionic liquid-supported solids, silica-supported solids, polymers, and MOFs. However, there are some shortcomings when exploiting the chemical fixation of CO 2 , such as the addition of organic solvent, the need for elevated pressure, harsh reaction conditions (high temperature and long reaction time), and/or low catalytic activity. , Thus, the development of new heterogeneous acidic catalysts to synthesize cyclic carbonates utilizing CO 2 as a building block is still of great interest. Moreover, developing a one-pot synthesis of cyclic carbonates from olefins and CO 2 is a highly desirable and economical approach because this reaction uses readily available olefins without the need for preliminary epoxide synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…They have also found an increase in CO 2 permeability, CO 2 selectivity with other gases. Yao et al 78 fabricated a chemically cross‐linked non‐metal MOF‐based MMM by incorporating imidazolium‐based IL and UiO‐66 nanoparticles. Besides finding improved CO 2 selectivity, permeation, and affinity over N 2 and CH 4 , they have also found that the membrane can act as a catalyst for CO 2 transformation by cycloaddition with epoxide under atmospheric pressure.…”
Section: Challenges and Research Trends For Mmmsmentioning
confidence: 99%
“…(Figure 4a) The membranes displayed high CO 2 permeance (up to 900 GPU, it is considerably 4.5 × 10 4 barrer at the membrane thickness of 50 μm), the CO 2 /N 2 selectivity of 45 and CO 2 /H 2 selectivity of 5.8, which exceeded the 2008 Robeson's upper bound line. Yao et al [53] constructed ILCMs by employing postsynthetic polymerization method of imidazolium-based ILs-decorated UiO-66 type nanoparticles and the isocyanate-terminated polyurethane oligomer. (Figure 4b) These membranes showed highly CO 2 /N 2 and CO 2 /CH 4 selectivities of 32.3 and 18.3 at 6 bar and 298 K, respectively.…”
Section: Ionic Liquid Based Composite Membranes (Ilcms)mentioning
confidence: 99%